Implantable cardioverter-defibrillators in sudden cardiac death prevention: guidelines and clinical practice (literature review) - I. V. Talibullin; N. B. Lebedeva (Бюллетень сибирской медицины, 2022)
Implantable cardioverter-defibrillators (ICDs) are considered to be the most beneficial in preventing sudden cardiac death (SCD), especially in patients with reduced left ventricular ejection fraction (LVEF). However, major large-scale randomized clinical trials on ICD effectiveness were conducted 20 years ago and do not reflect current realities. Modern ICDs and methods for treating heart failure have drastically improved. New clinical reality requires reconsideration of approaches to determining the risk of SCD and indications for ICD, personalization of device selection and programming, and identification of barriers that prevent ubiquitous use of the method in real clinical practice.The article reviews the available evidence base on the use of ICDs, current clinical guidelines, complications following the device implantation, and any difficulties associated with ICD application in routine clinical practice.